Sertraline accumulation and effects in the estuarine decapod Carcinusmaenas: Importance of the history of exposure to chemical stress - Rodrigues, Aurélie P. (2015)
Sertraline is widely prescribed worldwide and frequently detected in aquatic systems. There is, however, a remarkable gap of information on its potential impact on estuarine and coastal invertebrates. This study investigated sertraline accumulation and effects in Carcinus maenas. Crabs from a moderately contaminated (Lima) and a low-impacted (Minho) estuary were exposed to environmental and high levels of sertraline (0.05, 5, 500 μg L−1). A battery of biomarkers related to sertraline mode of action was employed to assess neurotransmission, energy metabolism, biotransformation and oxidative stress pathways. After a seven-day exposure, sertraline accumulation in crabs’ soft tissues was found in Lima (5 μg L−1: 15.3 ng L−1 ww; 500 μg L−1: 1010 ng L−1 ww) and Minho (500 μg L−1: 605 ng L−1 ww) animals. Lima crabs were also more sensitive to sertraline than those from Minho, exhibiting decreased acetylcholinesterase activity, indicative of ventilatory and locomotory dysfunction, inhibition of anti-oxidant enzymes and increased oxidative damage at ≥0.05 μg L−1. The Integrated Biomarker Response (IBR) index indicated their low health status. In addition, Minho crabs showed non-monotonic responses of acetylcholinesterase suggestive of hormesis. The results pointed an influence of the exposure history on differential sensitivity to sertraline and the need to perform evaluations with site-specific ecological receptors to increase relevance of risk estimations when extrapolating from laboratory to field conditions.